1979
DOI: 10.1021/jm00193a017
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and hypoglycemic activity of pyridylalcohols

Abstract: The potent hypoglycemic activity of 3-(3-methyl-2-pyridyl)propan-1-ol (1) prompted us to synthesize and study related structures. Some of the variables studied were the position of the methyl and alcohol side chains, the distance between the heterocyclic ring and the hydroxyl group, the effect of additional nuclear substitution, and the effects of branching and substitution on the alcohol side chain. The compounds were tested in 48-h fasted rats, usually at a dose of 150 mg/kg po. 1, the corresponding propioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
(39 reference statements)
1
2
0
Order By: Relevance
“…Finally, the preparation of pyridine 23 in good yield demonstrates the compatibility of alkene functionality with the cycloaddition and chlorination conditions. Structural assignments for the pyridine annulation products are based on NMR spectroscopic analyses, and data for the known pyridines 19 , 20 , 22 , and 24 are fully consistent with that previously reported for these compounds.…”
Section: Resultssupporting
confidence: 78%
“…Finally, the preparation of pyridine 23 in good yield demonstrates the compatibility of alkene functionality with the cycloaddition and chlorination conditions. Structural assignments for the pyridine annulation products are based on NMR spectroscopic analyses, and data for the known pyridines 19 , 20 , 22 , and 24 are fully consistent with that previously reported for these compounds.…”
Section: Resultssupporting
confidence: 78%
“…Blank et al [20] performed several structural modifications of 3-(3-methyl-2-pyridyl)-1-propanol (i, Figure 1), changing the positions of the methyl and alcohol side chains, the distance between the heterocycle and hydroxyl groups, and adding substituents, and they proved the hypoglycemic activity through animal experiments. Compounds were tested in rats fasted for 48 h at a dose of 150 mg/kg.…”
Section: Screening Of Hypoglycemic Heterocyclesmentioning
confidence: 99%
“…Attempts to alter the selectivity of this reaction failed, which indicated that competition between proton abstraction from the methylene group of ethyl orthobromoacetate and bromine displacement occurs. Treatment of the anion of (5) with bromoacetaldehyde diethyl acetal, however, gave high isolated yields of (12). It was found to be essential to use 1 equiv.…”
Section: (Ii) Methyl 3-(2-methoxy-4-pyridyl)propionatementioning
confidence: 99%